Debunking the obstacles to reporting workplace violence among the healthcare workers in Melaka, Malaysia: a qualitative study - Minhat, Halimatus Sakdiah; Sahiran, Mohammad Nafis (Universiti Putra Malaysia, 2024)
Introduction: Workplace violence (WPV) among healthcare workers (HCWs) is highly preventable and remains an ongoing public health concern among workers in Malaysia. Methods: Basic qualitative study design was employed to explore the individual experiences of healthcare workers with history of violence at workplace that hinders them to report the incidents. Informants were conveniently screened and identified based on underreporting of previous WPV experience, of any type. In-depth interviews among consented eligible HCWs were conducted using a semi-structured validated interview protocol. Transcribed data were thematically analyzed using an inductive approach. Results: A total of 11 informants and 11 coding were generated, with three themes emerged from the inductive thematic analysis, namely the perceived norms, process barriers, and attitude/ beliefs towards reporting WPV, with process barrier being the most frequently shared experience by the informants. Conclusion: The process barriers demotivate the HCWs from reporting the incidents, with their attitudes and beliefs shaped by their perceived norms towards WPVs among HCWs. Improvement of the existing reporting process is urgently needed. Training of workers is not only necessary to enhance their related knowledge and skills, but also to reduce the false belief and perceived norms towards WPV among HCWs.